Urbanisasi, Persebaran Penduduk dan Tata Ruang di Indonesia - Firman, Tommy (Journal of Regional and City Planning, 1996)
This article tries to discuss the relationship between urbanization, population dispersion, and spatial planning in Indonesia and also to assess the policy implication. Spatial planning in this context is the spatial distribution pattern of social economic, whereas urbanization in this context is the level of urban population compare to the entire population. In this regard, there should be a distinction between urbanization and urban development, the latter being the rate of increase in urban population, eventhough there is a strong relationship between the two. A Meanwhile, population dispersion is a form of natural resources dispersion and/or economic opportunity in a region.